Greek Palimpsests at Saint Catherine's Monastery (Sinai): Three Euchologia as Case Studies - Rossetto, Giulia (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
The Monastery of Saint Catherine in the Sinai peninsula preserves one of the largest collections of manuscripts in the world, which include a significant number of palimpsest manuscripts (over 170). This book deals with Saint Catherine's palimpsests in Greek language and offers their first-ever inventory. Three selected cases studies are then extensively described in order to showcase the richness and heterogenity of Sinai palimpsest books.